Diabetes mellitus type 2 risk in perimenopause - Cieślik-Guerra, Urszula; Drzewoski, Józef (Menopause Review/Przegląd Menopauzalny, 2009)
We can readily see the transition from curative to preventive medicine especially in relation to civilisation diseases. Diabetes and cardiovascular disease are inseparable because their risk factors and complications are intertwined with each other. This article is a short literature review about diabetes prevention in perimenopause when its risk is growing significantly, the same as cardiovascular diseases.